Alflutop Russian longitudinal multicenter observational study: use in patients with chronic back pain (message 3) - A. M. Lila; A. E. Karateev; L. I. Alexeeva; E. A. Taskina; An. B. Danilov; S. A. Zhivolupov; I. N. Samartsev; E. R. Barantsevich; A. P. Rachin (Современная ревматология)
The use of slow-acting disease-modifying symptomatic drugs, such as bioactive concentrate from small marine fish (BCSMF, Alflutop), is considered a potential element of complex therapy for chronic non-specific back pain (CNBP).Objective: to evaluate the efficacy of the BCSMF in patients with CNBP in real-life clinical practice.Material and methods. An open observational study included 10,047 patients with CNBP (age – 58.3±14.9 years, 58.4% women) with moderate or severe pain – 60 [50; 70] mm on the visual analogue scale (VAS). All patients received a course of BCSMF medication: 1 ml intramuscular (IM) daily No. 20 or 2 ml IM every other day No. 10. 68.8 % of patients also took non-steroidal anti-inflammatory drugs. Treatment outcomes were assessed 10 days after completion of BCSMF therapy (30 days after initiation of treatment).Results and discussion. As a treatment result, the pain intensity according to the VAS decreased from 60 [50; 70] to 20 [10; 30] mm (p<0.0001), the patients’ overall health assessment according to the VAS increased from 50 [30; 60] to 80 [60; 90] mm (p><0.0001) and the quality of life assessment (EQ-5D) – from 0.52 [0.06; 0.66] to 0.8 [0.71; 1] points (p>< 0.0001). A good response to treatment (pain reduction >50%) was observed in 73% of patients. On average, an improvement was observed on the 8th [5; 10] day of BCSMF therapy. There were no serious adverse effects associated with the use of the drug. Older age, overweight, initially more severe pain, and the presence of comorbid conditions were slightly more frequently associated with a less pronounced response to therapy.Conclusion. The use of BCSMF rapidly and effectively reduces the severity of pain and other symptoms associated with CNBP.